¿Elegir un destino por sus imágenes? - Cisneros Rivera, Nicol (2021)
In an era as technological as the current one, adapting to the needs of the environment is essential to survive market competition and this also applies to tourist destinations. Social media have become major channels for communicating destination image and achieve positioning. The image of the destination, shaped by the content generated and published on social networks by both the destination management and the users, is a key factor in the perceptions and decision-making of potential tourists. Given this, in this article, the concepts of destination management, web 3.0 and tourist destination image are initially defined, from which an international case and the reality of the issue at the national level are then addressed, to finally provide the conclusions of the analysis and some reflections.